Vaccination of chicken against Coccidiosis by using live Oocysts of different species of Eimeria - Mualla, A. A.; Yacoub, A. Y.; Kassab, A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was conducted to vaccinate chickens against coccidiosis  using alive vaccine contain seven species of chicken Eimeria,  E. tenella, E. brunetti, E. necatrix, E. maxima, E. mevati, E. acervulina  and E. praecox.    A total of 120 chicks were divided into two main groups: broiler group and egg laying group.  The birds of each group were allocated on to three pins, each contains 20 chicks.  The birds of the experiment were vaccinated at day nine of age, with a suspension of mixed Eimeria which contain 50 Oocysts of E. tenella with a different percent of other species, respectively.  The vaccine was given to chicks in the 1st pins of each group with drinking water,  the chicks in the 2nd pins were given vaccine by crop inoculation, while the chicks in the 3rd pins were left with no vaccine as a control group.  All groups were challenged at day 25 of age with 50000 sporulated Oocysts of live E. tenella with the same percentage of other species found in the suspension prepared, by crop inoculation. Clinical signs were observed, with the following parameters which were calculated; the mortality, Body weight gain, Oocysts count and protection rate. The results pointed out that the vaccinated chicks developed a resistance against Eimeria species present in the vaccine; by reducing clinical signs, mortality rate, and Oocysts count, with high protection rate especially among broilers, while weight gain was not affected especially among those vaccinated with drinking water. It was concluded that the prepared vaccine which was given to the chicks, at nine days of age decreases the severity of the disease, to avoid using high number of Oocysts in the vaccine